FENOMENA KONSUMSI BUDAYA KOREA PADA ANAK MUDA DI KOTA MANADO - Simbar, Frulyndese Karunia (HOLISTIK, Journal Of Social and Culture, 2016)
Global influence is the main thing of the spread of the culture, the various cultures of the developed countries on the continent of Europe and America has existed in Indonesia. Not only Western culture, but the culture of developed countries in Asia today have crowded in consumption by Indonesia, one example of a culture that is currently massively use by Indonesian society is the culture south Korea, which was known as hallyu or Korean wave. Hallyu is quickly and surely come and stay into the Indonesian community life especially in the hearts of young people. With their products that are very simple but always full of innovations, hallyu has now becoming one of the youth culture in Indonesia. Iin several major cities in Indonesia hallyu’s products became the most important thing of the young people, it is also entered in the city of Manado, hallyu or Korean wave has become one of the phenomena, which is the young people who are the nation's future is now using and adoring the product of outside, without thinking to use domestic products. This study aims to determine of how the hallyu’s product consume by the young people in Manado and the reason that why Korean Wave has been choose by them to be consume massively than Indonesia products Keywords: hallyu, Korean Wave, Manado.